Alveolar echinococcosis as a cause of vertebral osteomyelitis and soft tissue infection with recurrent cutaneous fistula formation - Kirsten Schmidt-Hellerau; Kerstin Reiners; Ayla Yagdiran; Nicolaus Friedrichs; Julia Fischer; Gerd Fätkenheuer; Clara Lehmann; Norma Jung (International Journal of Infectious Diseases, 2022)
Echinococcus multilocularis is endemic in Germany. However, alveolar echinococcosis is a rare disease. Most commonly the parasite affects the liver, behaving like a malignant tumour. Bones are affected in less than 2% of cases. We report a case of vertebral osteomyelitis accompanied by recurrent cutaneous fistula formation.